PENGARUH LDR, DAN BOPO TERHADAP ROA DENGAN NIM SEBAGAI VARIABEL INTERVENING Studi pada Bank Umum di Indonesia Periode Tahun 2011-2013 - Widhian Hardiyanti; Bogy Febriatmoko (Dinamika Akuntansi Keuangan dan Perbankan, 2016)
This study is performed to test the effect of LDR, and BOPO toward NIM to increase ROA. The objective to analyze the effect of the bank financial ratios performance (LDR and BOPO) toward NIM to increase ROA in banking industry over period 2011-2013. Sampling technique used here is pusposive sampling. The data was taken Otoritas Jasa Keuangan (OJK). It is gained sample amount of 114 data. The analysis technique used here is multiple regression with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and f-statistic to examine the mean of mutual effect with level of significance 5%. In addition, classical assumption is also performed including normality test, multicolinearity test, and heteroscedasticity test. The result shows LDR and BOPO to have influence toward NIM at level of significance less than 5%, and LDR and BOPO, and NIM have influence toward ROA at level of significance more than 5%. Key words:LDR, BOPO, ROA, Net interest margin